Carcass merit project: development of EPDS and genetic marker validation - Pollak, E.J.; Green, R.D.; Taylor, J.; Davis, S.; Holm, T.; Koontz, S.; Gill, C.; Moser, Daniel W.; Westcott, E.A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Carcass and Warner-Bratzler shear force data on strip loin steaks have been obtained on over 4,200 cattle from contemporary progeny groups from the most widely used sires in 15 beef cattle breed associations (16 breeds). Trained sensory panel evaluations have been conducted on over 1,500 strip loin steaks from a sample of contemporary progeny groups from sires included in the QTL (quantitative trait loci) validation component of the project. One breed association has published Warner-Bratzler shear force Expected Progeny Differences (EPDs) for 57 sires of two breeds. DNA analyses and screening have been completed for 11 QTL on eight sires from several breeds. EPDs for carcass traits, Warner-Bratzler shear force, and sensory panel traits may be completed for several breeds within the year 2001. Information from this project should allow seedstock producers to improve carcass traits, tenderness, and other palatability traits through classical genetic selection or through DNA marker-assisted selection.
Keywords: Beef; Carcass merit; EPDS; Genetic marker